Effects of thinning and understory removal on soil phosphorus fractions in subtropical pine plantations - Jian, Zunji; Zeng, Lixiong; Lei, Lei; Liu, Changfu; Shen, Yafei; Zhang, Jiajia; Xiao, Wenfa; Li, Mai-He (Frontiers in Plant Science, 2024)
Forest management changes the physical environments and nutrient dynamics and then regulates the forest productivity. Soil phosphorus (P) availability is critical for productivity in tropical and subtropical forests. However, it was still poorly understood how soil P content and fraction respond to various forest management practices in these regions. Here, we measured the soil total P, available P, and Hedley’s P fractions, including inorganic and organic P (Pi and Po), in subtropical pine plantations treated with understory removal (UR), non-dominant species thinning (NDST) and dominant species thinning (DST) after nine years. Compared to plantations without management (CK), treatments such as UR, NDST, and DST decreased soil total P at 0–10 cm and soil available P at 0–10 cm and 10–20 cm. Increases in resin-Pi, NaOH-Pi, and C.HCl-Pi resulted in a higher total Pi in 0–10 cm (p < 0.05) in treated plots (UR, NDST, and DST) than in CK plots. UR, NDST, and DST treatments increased NaHCO3-Po and NaOH-Po (p < 0.05) but decreased C.HCl-Po at a depth of 0–10 cm. Regardless of management treatments, soil total P, available P, and P fractions in 0–10 cm showed higher contents than those in 10–20 cm. There were positive relationships between total P and total Po (p < 0.01) and between available P and total Pi. There were also positive relationships between total P, available P, NaHCO3-Pi, and NaOH-Pi (p < 0.05). In conclusion, forest management such as UR, NDST, and DST decreased soil total P and available P, and transforming soil P fractions to available P will meet the P demand following management in the pine plantations of subtropical China.